A Sample of Edge-on H i-rich Low Surface Brightness Galaxy Candidates in the 40% ALFALFA Catalog - He, Min; Wu, Hong; Du, Wei; Liu, He-yang; Lei, Feng-jie; Zhao, Pin-song; Zhang, Bing-qing (The Astrophysical journal. Supplement series, 2020)
Low surface brightness galaxies (LSBGs) are defined as galaxies that are fainter than dark night sky and are important for studying our universe. Particularly, edge-on galaxies are useful for the study of rotational velocity and dynamical properties of galaxies. Hence here we focus on searching for edge-on LSBGs. In order to find these edge-on dim galaxies, a series of effects caused by inclination, including the surface brightness profile, internal extinction, and scale length, have been corrected. In this work, we present a catalog of 281 edge-on LSBG candidates, which are selected from the crossmatch between Sloan Digital Sky Survey Data Release 7 and the 40% ALFALFA catalog. We also present the properties of these edge-on LSBG candidates including the absolute magnitude, central surface brightness, B − V color, scale length, and relative thickness. Our result suggests that the correction of inclination effects is very important for obtaining a complete sample of LSBGs.